2021
DOI: 10.1038/s41598-021-83913-7
|View full text |Cite
|
Sign up to set email alerts
|

CIBERSORT analysis of TCGA and METABRIC identifies subgroups with better outcomes in triple negative breast cancer

Abstract: Studies have shown that the presence of tumor infiltrating lymphocytes (TILs) in Triple Negative Breast Cancer (TNBC) is associated with better prognosis. However, the molecular mechanisms underlying these immune cell differences are not well delineated. In this study, analysis of hematoxylin and eosin images from The Cancer Genome Atlas (TCGA) breast cancer cohort failed to show a prognostic benefit of TILs in TNBC, whereas CIBERSORT analysis, which quantifies the proportion of each immune cell type, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 99 publications
1
57
0
Order By: Relevance
“…This method relies on linear support vector regression (SVR), a machine learning approach to deconvolute the gene expression signatures, known as "signature matrix" for determining the relative fraction of immune cell proportions in blood or tissues (15). The CIBERSORT method has been widely used to infer immune cell types from transcriptomics data to predict outcomes of different cancers (9,43,44) and infectious diseases (45)(46)(47). In this study, the CIBERSORT output identified the downregulation of "CD8 + T cells" in patients with PTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method relies on linear support vector regression (SVR), a machine learning approach to deconvolute the gene expression signatures, known as "signature matrix" for determining the relative fraction of immune cell proportions in blood or tissues (15). The CIBERSORT method has been widely used to infer immune cell types from transcriptomics data to predict outcomes of different cancers (9,43,44) and infectious diseases (45)(46)(47). In this study, the CIBERSORT output identified the downregulation of "CD8 + T cells" in patients with PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in statistical modeling and bioinformatics approaches have accelerated the identification of disease-centric genes by employing gene networking methods based on graph topological parameters for many infectious diseases (7,8). Moreover, the new bioinformatic methods like estimating relative subsets of RNA transcripts (CIBERSORT), Tumor Immune Estimation Resource (TIMER), and Estimating the Proportions of Immune and Cancer cells (EPIC) are developed to characterize immune cell composition using large-scale gene expression data (9,10). These bioinformatic methods implement functional enrichment scores based on the presence of the query genes over reference gene sets.…”
Section: Introductionmentioning
confidence: 99%
“…Craven et al. ( 67 ) reported that PKD1 was more frequently mutated in a group enriched in both CD8 + T cells and CD4 memory-activated T cells in triple-negative breast cancer. Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Following the CIBERSORTx manual, we set the number of permutations to 100. We uploaded RNA-seq FPKM data and set quantile normalization to discern the recommended setting ( Craven et al, 2021 ). We filtered out immune cell types with an average proportion lower than 2%, and 14 types of immune cells were included into the final analysis.…”
Section: Methodsmentioning
confidence: 99%